2022
DOI: 10.3390/cancers14030565
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcome of Elderly Patients (>55 Years) with Acute Lymphoblastic Leukemia

Abstract: Prognosis of elderly ALL patients remains dismal. Here, we retrospectively analyzed the course of 93 patients >55 years with B-precursor (n = 88) or T-ALL (n = 5), who received age-adapted, pediatric-inspired chemotherapy regimens at our center between May 2003 and October 2020. The median age at diagnosis was 65.7 years, and surviving patients had a median follow-up of 3.7 years. CR after induction therapy was documented in 76.5%, while the rate of treatment-related death within 100 days was 6.4%. The OS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Matthias Stelljes, M.D. : Older patients with ALL have historically had poor outcomes when treated with conventional chemotherapy, with 5-year survival rates of approximately 20% [ 1 4 ]. Numerous factors contribute to low survival rates compared to younger patients, including adverse disease biology among older patients, like high-risk genetic alterations, but the major issue is the poor tolerance to intensive chemotherapy regimens, most likely due to the presence of comorbidities, high rates of early deaths, and treatment-related mortality in remission [ 1 , 2 ].…”
Section: Transcriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Matthias Stelljes, M.D. : Older patients with ALL have historically had poor outcomes when treated with conventional chemotherapy, with 5-year survival rates of approximately 20% [ 1 4 ]. Numerous factors contribute to low survival rates compared to younger patients, including adverse disease biology among older patients, like high-risk genetic alterations, but the major issue is the poor tolerance to intensive chemotherapy regimens, most likely due to the presence of comorbidities, high rates of early deaths, and treatment-related mortality in remission [ 1 , 2 ].…”
Section: Transcriptmentioning
confidence: 99%
“…Attempts to decrease intensity of therapy have improved treatment-related mortality, but the trade-off associated with this approach is higher rates of relapse [ 5 ]. We recently published a retrospective analysis of the course of 93 patients aged older than 55 years of age with ALL who received age-adapted, pediatric-inspired chemotherapy regimens at our center between May 2003 and October 2020 [ 4 ]. We found that intensive treatment is feasible in the selected elderly patient population, but the outcomes seemed to have improved only modestly as a conventional therapy.…”
Section: Transcriptmentioning
confidence: 99%
“…The introduction of pediatric-inspired regimens has improved outcomes remarkably in both B-cell precursor (BCP) acute lymphoblastic leukemia (ALL) and T-ALL, with 5-year overall survival rates approaching 60% in patients <55 years old 1 and between 35% and 55% in older patients. 2 Nevertheless, disease relapse and chemo-refractoriness (R/R) are still clinical problems, especially in T-ALL, for which very few novel drugs are available, and in BCP-ALL patients who fail to respond to or relapse after chemo-immunotherapy. 3 Selective inhibition of BCL-2 with venetoclax and inhibition of BCL-2 and BCL-XL with navitoclax directly releases apoptosis activators from pro-apoptotic proteins, causing permeabilization of the mitochondrial outer membrane, leading to cell death.…”
Section: Bh3 Mimetics In Relapsed and Refractory Adult Acute Lymphobl...mentioning
confidence: 99%
“…The prognosis of relapsed or refractory (r/r) acute lymphoblastic leukemia (ALL) remains dismal to date and worsens with age [ 1 ]. 20%–40% of patients relapse after allogeneic hematopoietic cell transplantation (alloHCT), with a median overall survival (OS) of only 5.5 months [ 2 ].…”
Section: Introductionmentioning
confidence: 99%